2016
DOI: 10.1111/his.13022
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional microscopic analysis of clinical prostate specimens

Abstract: In conclusion, the applicability of 3D imaging to archival FFPE and fresh clinical specimens offers unlimited opportunities to study clinical and biological topics of interest in their actual 3D context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 23 publications
3
74
0
2
Order By: Relevance
“…The Gleason grading system underwent further specifications, orchestrated by the International Society of Urological Pathology (ISUP), that aimed to standardize current practice which, over the years, had begun to deviate from the original description by Donald Gleason [24,25,26]. Despite all efforts, it must be said that the interobserver variability of this powerful grading system was, and remains, moderate, and that further work is necessary to harmonize the human perception of morphological patterns [27,28,29], or support it with computer-assisted analysis [30,31]. Alternatively, molecular markers may come to our aid to improve our classification of prostate cancer.…”
Section: Spatial and Morphological Heterogeneity Of Prostate Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…The Gleason grading system underwent further specifications, orchestrated by the International Society of Urological Pathology (ISUP), that aimed to standardize current practice which, over the years, had begun to deviate from the original description by Donald Gleason [24,25,26]. Despite all efforts, it must be said that the interobserver variability of this powerful grading system was, and remains, moderate, and that further work is necessary to harmonize the human perception of morphological patterns [27,28,29], or support it with computer-assisted analysis [30,31]. Alternatively, molecular markers may come to our aid to improve our classification of prostate cancer.…”
Section: Spatial and Morphological Heterogeneity Of Prostate Cancermentioning
confidence: 99%
“…The genetic mechanisms are relatively well-understood, but the relationship between the clones and their spatial distribution are not clear. Some insights could be acquired from the most recent study on the architecture of prostate cancer [31], which showed that prostate cancer comprises a complex integrative structure of intercommunicating tubules. This implies that, regionally at least, there is an epithelial continuity of all the structural elements (glands).…”
Section: Genetic/molecular Heterogeneitymentioning
confidence: 99%
“…In addition, Van Royen et al using BABB clearing could further apply immuno-histochemistry to cleared prostate biopsies followed by confocal microscopy. Of interest, the authors note that the cleared specimens retained a high DNA yield and could further be subjected to a polymerase chain reaction [42]. The extent of tissue clearing techniques application towards the field of cancer is not limited to its clinical applications.…”
Section: What the Future Holdsmentioning
confidence: 99%
“…Das Gleason-Graduierungssystem erfuhr weitere Verfeinerungen, die von der International Society of Urological Pathology (ISUP) zusammengetragen und beschrieben wurden, um die derzeitige Praxis, die im Laufe der Jahre von der ursprünglichen Beschreibung von Donald Gleason abgewichen war, zu beschreiben und zu standardisieren [24][25][26]. Trotz aller Bemühungen muss gesagt werden, dass die Untersucherübereinstimmung auch dieses prognostisch mächtigen Graduierungssystems nur moderat war und bleibt, und dass weitere Arbeit notwendig ist, um die menschliche Wahrnehmung morphologischer Muster zu harmonisieren [27][28][29] oder durch computergestützte Analyse zu unterstützen [30,31]. Alternativ kön-nen uns künftig vielleicht molekulare Marker dabei helfen, unsere Klassifikation des Prostatakrebses zu verbessern.…”
Section: Morphologische Heterogenitätunclassified
“…Die genetischen Mechanismen sind relativ gut verstanden, aber die Beziehung zwischen den Klonen und ihre räumliche Verteilung sind nicht klar. Einige Erkenntnisse konnten aus der jüngsten Studie über die Architektur des Prostatakrebses gewonnen werden [31], die zeigte, dass der Prostatakrebs eine komplexe integrative Struktur von interkommunizierenden Tubuli umfasst. Dies impliziert, dass zumindest regional eine epitheliale Kontinuität aller Strukturelemente (Drüsen) besteht.…”
Section: Ein Kurzer üBerblick üBer Die Genetik Des Prostatakrebsesunclassified